A retrospective comparative study: Novel diagnostical markers of inflammation and cardiovascular risk of bipolar disorder and manic episode (Annals of Medical Research, 2025)
Aim: The pan-immune inflammation value (PIV), inflammation burden index (IBI), atherogenic index of plasma (AIP), neutrophil/ high-density lipoprotein (HDL) ratio (NHR), lymphocyte/HDL ratio (LHR), monocyte/HDL ratio (MHR), and platelet/HDL ratio (PHR) have recently been investigated as novel inflammatory and cardiovascular markers. Our study aimed to compare these indices with the manic episode and remission period of bipolar disorder (BD) patients with controls and to investigate the relationship between these indices and the clinical characteristics of the patients and whether these indices can be biomarkers for the disease and manic episode.Materials and Methods: In this retrospective observational study, we collected data from 66 patients in remission, 67 patients with manic episodes, and 70 controls. Differences in PIV, IBI, AIP, NHR, MHR, LHR, and PHR were investigated.  We performed logistic regression analysis to identify predictors of manic episodes, and the diagnostic potential of these parameters was evaluated using ROC curves.Results: Significant differences were found between the three groups in NHR (p
Keywords: Pan-immune-inflammation value; Inflammatory burden index; Atherogenic index of plasma; Bipolar disorder; Biomarker